The quality of the educational service and the loyalty of students from private institutes Surco - Silva Mendoza, Alejandra Estela (2022)
Achieving a quality educational service is a priority to take into account in the training of students of the Peruvian institutes of higher education, since by doing so these institutions retain their students so that they finish the degree and contribute to the development of society and in The objective of this research was to determine the technical superior educational quality and the relationship it has with the loyalty of the students of the banking school of private institutes of Surco, the survey tool was also used in a group of 129 students of the mentioned school and the results showed that the levels of loyalty are affected by the dimensions that make up the quality of the educational service. On the other hand, the Pearson Chi-Square Test and the Spearman Correlation Test were used to test the hypothesis. Finally, the results of these tests showed a significant high correlation between quality educational service and student loyalty.